Some teacher and vocational variables as correlates of attitudes to social studies teaching at the basic education level in southern Nigeria (2008)
Studies on attitudes have focused mainly on the role they play in students' learning and achievement. This study investigated teachers' attitude, since teachers form an important component of any educational system. Specifically, the study focused on some teacher and locational variablea as they influence teachers' attitudes to teaching social studies at the basic level of education. The study was carried out in the three geo-political zones that make up southern nigeria. The sample consisted of 903 primary school teachers made up of 383 males and 520 female. One instrument developed and validated by the researcher was used for data collection. The data collected were analysed using descriptive and inferential statistics such as frequency counts, percentages and chi-square statistics. Findings reveal that the teachers seem to be negatively predisposed tot eaching social studies. Also, while gender and geographical zones of respondents influenced the attitudes of practising primary school teachers to teaching socail studies, age did not. Unexpectedly, findings also show that a large proportion of professionally trained teachers are negatively predisposed to teaching social studies. Also, while gender and geographical zones of respondents influenced the attitudes of practising primary school teachers to teaching social studies, age did not. Unexpectedly, findings also show that a large proportion of professionally trained teachers are negetively prediposed to teaching social studies. This has implications for teaacher training and development. Suggestions were made towards improving teachers' attitudes and invariably improving teaching effectiveness in social studies at the basic level of education in Nigeria.